(untitled) (International Journal of Physiotherapy, 2020)
Objective: The objective of this study was to find out whether there was any shoulder instability prevailing in the shot put throwers due to the rotational activities achieved in the respective sport. Methods: A total of 76 shot put throwers were recruited for the study. The multidirectional instability of the shoulder joint was tested by performing special tests. Results: The study revealed that out of 76 shot put throwers, 49 individuals were found to be having shoulder instability, and 27 individuals were not having shoulder instability. This was confirmed by using a special test like the Sulcus sign and Rowe test followed by statistical analysis. The individuals diagnosed with multidirectional instability showed Sulcus sign and Rowe test positive, of which 30 individuals showed both the test positive and 19 individuals showed only Rowe test positive. Conclusion: About 64.47% of individuals were diagnosed with multidirectional instability in the shot put throwers while the rest 35.52% of individuals showed no signs of instability.